2022
DOI: 10.1007/s12144-022-02843-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural assessment and comparisons of risk tolerance across domains

Abstract: Risk attitudes are known to play an important role in influencing one’s behavior under conditions of uncertainty. To date, cultural influences on risk attitudes - beyond the effects they have on perceived risk - have not been well understood. Having a cross-culturally invariant measure of risk attitudes is a prerequisite for carrying out more in depth explorations in this area. The current study applied the domain-specific risk attitudes framework and focused on the Chinese and US cultural contexts. Using nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…However, contrary to expectations, studies have suggested that Chinese people, despite being collectivistic individuals, have a higher financial risk tolerance than Americans. These findings are based on the cushion hypothesis, which indicates that in collectivistic cultures, people have a stronger social network that provides more financial help for those in need ( Hsee and Weber, 1999 ; Shou et al., 2022 ). Shou et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, contrary to expectations, studies have suggested that Chinese people, despite being collectivistic individuals, have a higher financial risk tolerance than Americans. These findings are based on the cushion hypothesis, which indicates that in collectivistic cultures, people have a stronger social network that provides more financial help for those in need ( Hsee and Weber, 1999 ; Shou et al., 2022 ). Shou et al.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are based on the cushion hypothesis, which indicates that in collectivistic cultures, people have a stronger social network that provides more financial help for those in need ( Hsee and Weber, 1999 ; Shou et al., 2022 ). Shou et al. (2022) suggest that this could also apply to health contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to culture, studies of (Statman & Weng, 2010) show how cultural factors can have effect in the risk tolerance of investors. Also, studies of (Amirhosseini & Okere, 2012), (Shou, Olney, & Wang, 2022) show the relationship between cultural factors and risk tolerance. However, there has not been the inclusive study in this topic covering all the factors in one paper.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, it was explained that exploring the impact of cultural diversity is important for development of effective project management approaches in multinational teams and they may become effective instruments for improving cooperation and organization productivity (Pavez et al, 2022;Rodríguez-Rivero et al, 2020). Therefore, critical assessment of cultural influences on project management may positively change communication styles (Szpilko et al, 2022), risk tolerance (Rodríguez-Rivero et al, 2020;Shou et al, 2023), motivation of employees (Dasí et al, 2021), and relationship building (Tian, 2020). In addition, effective culturally diverse teams lead to introduction of innovations (Jones et al, 2020), offer modernization strategies to transition of business processes to the conditions of global environment (Burkiewicz & Knap-Stefaniuk, 2022;Onyusheva et al, 2020), and eliminate unnecessary, or redundant tasks (Duchek et al, 2020;Hu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%